A novel method to visualise the three‐dimensional organisation of the human cerebral cortical vasculature. Issue 6 (9th March 2018) - Harrison, C. H.; Buckland, G. R.; Brooks, S. E.; Johnston, D. A.; Chatelet, D. S.; Liu, A. K. L.; Gentleman, S. M.; Boche, D.; Nicoll, J. A. R.
Abstract: Current tissue‐clearing protocols for imaging in three dimensions (3D) are typically applied to optimally fixed, small‐volume rodent brain tissue – which is not representative of the tissue found in diagnostic neuropathology laboratories. We present a method to visualise the cerebral cortical vasculature in 3D in human post‐mortem brain tissue which had been preserved in formalin for many years. Tissue blocks of cerebral cortex from two control cases, two Alzheimer's brains and two cases from Alzheimer's patients immunised against Aβ42 were stained with fluorescent Lycopersicon esculentum agglutinin (Tomato lectin), dehydrated and cleared using an adapted three‐dimensional imaging of solvent cleared organs (3DISCO) protocol to visualise the vascular endothelium. Tissue was imaged using light sheet and confocal microscopy and reconstructed in 3D usingamira software. The method permits visualisation of the arrangement of the parallel penetrating cortical vasculature in the human brain. The presence of four vascular features including anastomosis, U‐shaped vessels, spiralling and loops were revealed. In summary, we present a low cost and simple method to visualise the human cerebral vasculature in 3D compatible with prolonged fixation times (years), allowing study of vascular involvement in a range of normative and pathological states.